Becoming a Guest: Christology and Ecclesiological Identity - De Vries, Roland (Théologiques)

(untitled) (Faculté de théologie et de sciences des religions, Université de Montréal, 2017)
The question of ecclesiological identity is a pressing one in the contemporary context, particularly in the light of the church’s increasing marginalization or relative insignificance within Western society. This question of ecclesiological identity is explored by way of engagement with the guest Christology of the Nigerian Presbyterian theologian Enyi Ben Udoh, and by way of John Koenig’s New Testament Hospitality. The result is a suggestive and constructive vision of the church that prioritizes its status as guest, in relation to the Christ who comes to the human family as guest, then kin, then Lord. The implications of this guest Christology for the church are sketched in conclusion.